A dimensão técnico-operativa do Serviço Social: um estudo com assistentes sociais inseridos na política de assistência social do município de Aracaju/SE - Santos, Suellen Emilly dos (2020)
The present study aims to understand the technical-operative dimension of Social Work from the conceptions of social workers inserted in the equipment Reference Center for Social Assistance-CRAS and Specialized Reference Center for Social Assistance-CREAS in the municipality of Aracaju. The general objective is to analyze the technical-operative dimension from the professional practice of social workers inserted in the CRAS and CREAS of Aracaju. The specific objectives are: to contextualize the debate on the technical operational dimension within the scope of the Brazilian Social Service; contextualize the historical trajectory of social assistance in the Brazilian reality; and apprehend the technical-operative dimension of the professional practice of social workers inserted in CRAS and CREAS in Aracaju. This is a study supported by the dialectical historical materialist method, which used field research as methodology based on semi-structured interviews with nine social workers. Among the main results achieved from the data analysis, we can highlight: the conceptions of these professionals about the technical-operative, theoretical-methodological, ethical-political and investigative dimension, of which five interviewees highlighted the importance of these dimensions being articulated in professional practice, one highlighted not having knowledge about this discussion and three reported about the dimensions, but did not speak about the articulation. Of these three professionals, two highlighted the difficulties they had in professional practice to understand this articulation between dimensions; another point highlighted were the main demands of professional practice. For professionals working at CRAS, the granting of occasional benefits was considered the main demand; CREAS social workers highlighted the care for vulnerable groups (women, the elderly and children). The main responses of these professionals to these demands was monitoring, welcoming, home visits and groups. From the analyzes carried out, we also understand that the technical-operative dimension of the social workers at CRAS and CREAS in Aracaju is permeated by many limits, especially in this current scenario of cuts in social rights, in which the number of demands increases at the time when the resources available for the materialization of social rights end up being scarce. In this way, the professionals end up being challenged to create strategies that strengthen the technical-operative dimension and its objectification in a qualified way on a daily basis.